Analisis Perbandingan Kinerja Keuangan Pada Perusahaan Property Dan Real Estate Yang Terdaftar Di BEI Sebelum Dan Saat Pandemi Covid-19 - Febri Oktafira; Andoni Fornio Barusman (UNIVED Press, 2022)
The COVID-19 pandemic has had a destructive effect at the property and real estate sector. Through studying the corporation's monetary statements, some of techniques may be recognized a good way to allow the business enterprise to live on in the COVID-19 pandemic situation. This study ambitions to determine the financial overall performance of actual property and real estate businesses listed at the Indonesian stock change earlier than and at some stage in the 2018-2020 duration of the Covid-19 pandemic. Using economic and comparative evaluation as a studies method. The effects of studies on properties and real estate agencies listed on the IDX earlier than and during the pandemic determined no widespread distinction among CR 2018 and 2019 with 2020, DAR 2018 with 2020 and TATO 2019 with 2020. In the meantime, there was a widespread distinction. DAR in 2019 with 2020, NPM in 2018 and 2019 with 2020 and TATO in 2018 with 2020. Thus, it can be seen that the most affected by the pandemic in property and real estate companies listed on the IDX Exchange is the level of profitability as indicated by a decrease in NPM through financial ratio analysis and significant differences are obtained through paired sample tests.